Markov chain modeling for immunological status of HIV patients. Issue 2 (3rd April 2019) - Deneshkumar, V.; Manoprabha, M.; Senthamarai Kannan, K.
Abstract: CD4 cell count test is used to monitor the immunological status of the immune system. We took an attempt to check the efficacy of a HIV treatment based on the progression of CD4 cell count by means of higher order Markov chain. The main objective of this article is to study HIV disease progression using higher order Markov chain to determine the dependency between the current states of the patient to the previous states. The best model has been evaluated using EDC and LRT.